2011
DOI: 10.1111/j.1464-410x.2011.10490.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcapsular renal haematoma after holmium:yttrium‐aluminum‐garnet laser ureterolithotripsy

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? The literature scarcely reports subcapsular renal haematoma (SRH) after lithotripsy techniques. We reported the incidence, associated risk factors, possible pathogenesis, precautions, and outcomes of SRH after ureteroscopic lithotripsy (URSL). OBJECTIVE To report the incidence, risk factors, and outcomes of subcapsular renal haematoma (SRH) after ureteroscopic lithotripsy (URSL) using holmium:yttri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 8 publications
(13 reference statements)
3
55
1
1
Order By: Relevance
“…The incidence of RSHs after URSL in the present series was 0.4%, significantly higher than in those reported in the review by Blute et al [3], significantly lower than in those reported in the review by Bai et al [6]. A possible explanation could be the fact that Bai et al [6] systematically inserted a double J stent, and so did we mostly.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…The incidence of RSHs after URSL in the present series was 0.4%, significantly higher than in those reported in the review by Blute et al [3], significantly lower than in those reported in the review by Bai et al [6]. A possible explanation could be the fact that Bai et al [6] systematically inserted a double J stent, and so did we mostly.…”
Section: Discussioncontrasting
confidence: 56%
“…Some patients have continuous flank pain after placement of a double J stent, and not only during voiding. This could explain the higher incidence of technical investigations and detection of hematoma in our population and in that of Bai et al [6]. …”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…[1][2][3] While both a lumbar artery branch rupture and a SRH can present with unexplained decreasing hematocrit or flank pain, the timing of onset of the symptoms may vary depending on the nature of the injury. Our patient presented with hypotension, tachycardia, and a decreasing hematocrit in the immediate postoperative period due to the severe nature of the hemorrhage; on the …”
Section: Discussionmentioning
confidence: 99%